2016
DOI: 10.3389/fcell.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Glutathione Status in Type 2 Diabetics with Vitamin B12 Deficiency

Abstract: Deficiencies in vitamin B12 and glutathione (GSH) are associated with a number of diseases including type 2 diabetes mellitus. We tested newly diagnosed Indian diabetic patients for correlation between their vitamin B12 and GSH, and found it to be weak. Here we seek to examine the theoretical dependence of GSH on vitamin B12 with a mathematical model of 1-carbon metabolism due to Reed and co-workers. We study the methionine cycle of the Reed-Nijhout model by developing a simple “stylized model” that captures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…In 2019 demonstrated the administration of vitamin B12 to male rats prevents the androgenic failure and counteracts the damage inflicted by cimetidine (including DNA fragmentation) upon sperm quality (Beltrame et al., 2019). Recent studies have shown that vitamin B12 modulated oxidative stress responses through the increasing methionine synthase activity related to glutathione synthesis (Karamshetty et al., 2016; Manzanares & Hardy, 2010). Glutathione synthesis is a major intracellular antioxidant which play an important functions in the intracellular protective mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019 demonstrated the administration of vitamin B12 to male rats prevents the androgenic failure and counteracts the damage inflicted by cimetidine (including DNA fragmentation) upon sperm quality (Beltrame et al., 2019). Recent studies have shown that vitamin B12 modulated oxidative stress responses through the increasing methionine synthase activity related to glutathione synthesis (Karamshetty et al., 2016; Manzanares & Hardy, 2010). Glutathione synthesis is a major intracellular antioxidant which play an important functions in the intracellular protective mechanism against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, B12 may indirectly stimulate ROS scavenging by preservation of glutathione, which likely involves an intricate network of reactions that has not been fully elucidated [ 6 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy of an octopus arm is composed almost entirely of muscle and connective tissue 27 (Fig. 1 ), minimizing mechanical constraints of physical anatomy.…”
Section: Discussionmentioning
confidence: 99%